1993
DOI: 10.2307/1940086
|View full text |Cite
|
Sign up to set email alerts
|

Wood Decomposition: Nitrogen and Phosphorus Dynamics in Relation to Extracellular Enzyme Activity

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 169.230.243.252 on Sun, Abstract.Because plant litter decomposition is directly mediated by extracellular enzymes (ectoenzymes), analyses of the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
178
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(199 citation statements)
references
References 18 publications
17
178
0
4
Order By: Relevance
“…Specifically, two N cycling enzymes, β-N-acetyl-glucosaminidase and leucine aminopeptidase that are respectively involved in the degradation of chitin and the degradation of proteins and peptides, are mentioned mostly in available literature (DeForest et al 2012;Enowashu et al 2009). Sinsabaugh et al (1993) assumed that low N availability could induce the activity of β-N-acetyl-glucosaminidase while high N availability may result in a noncompetitive inhibition. For example, Enowashu et al (2009) reported that the activities of N cycling enzymes such as urease, arginine, deaminase, alanyl aminopeptidase, and lysyl-alanyl aminopeptidase increased, but the activities of β-N-acetyl-glucosaminidase and leucine aminopeptidase were found to decrease in a spruce forest under reduced N deposition conditions.…”
Section: N Mineralizationmentioning
confidence: 99%
“…Specifically, two N cycling enzymes, β-N-acetyl-glucosaminidase and leucine aminopeptidase that are respectively involved in the degradation of chitin and the degradation of proteins and peptides, are mentioned mostly in available literature (DeForest et al 2012;Enowashu et al 2009). Sinsabaugh et al (1993) assumed that low N availability could induce the activity of β-N-acetyl-glucosaminidase while high N availability may result in a noncompetitive inhibition. For example, Enowashu et al (2009) reported that the activities of N cycling enzymes such as urease, arginine, deaminase, alanyl aminopeptidase, and lysyl-alanyl aminopeptidase increased, but the activities of β-N-acetyl-glucosaminidase and leucine aminopeptidase were found to decrease in a spruce forest under reduced N deposition conditions.…”
Section: N Mineralizationmentioning
confidence: 99%
“…This study shows that apart from chitinase activities, conversion of peatland for agricultural use resulted in a reduction of β-glucosidase, cellobiohydrolase and acid phosphatase activities. The relatively high chitinase activity suggests a high metabolic demand for N released during chitin turnover [49]. Although not significantly different, the slightly higher acid phosphatase activity in NF and RP soils may have be driven by microbial C demand, considering the relatively large P-availability [50].…”
Section: Effects Of Land-use On Soil Enzyme Activitiesmentioning
confidence: 85%
“…Phosphate was not a growth-limiting nutrient in the culture system, it was easily available in sufficient quantities and it might even accumulate in mycorrhizal mycelium (Colpaert & Van Tichelen, 1996). At high levels of P availability, micro-organisms probably expend less energy in extracellular phos-phatase production to acquire P from organic sources (Sinsabaugh et al, 1993). Inorganic P can be a good repressor of phosphatase production in ectomycorrhizal fungi (Bousquet, Mousain & Salsac, 1986).…”
Section: Discussionmentioning
confidence: 99%